2018
DOI: 10.5853/jos.2017.02922
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Small Vessel Disease: A Review Focusing on Pathophysiology, Biomarkers, and Machine Learning Strategies

Abstract: Cerebral small vessel disease (cSVD) has a crucial role in lacunar stroke and brain hemorrhages and is a leading cause of cognitive decline and functional loss in elderly patients. Based on underlying pathophysiology, cSVD can be subdivided into amyloidal and non-amyloidal subtypes. Genetic factors of cSVD play a pivotal role in terms of unraveling molecular mechanism. An important pathophysiological mechanism of cSVD is blood-brain barrier leakage and endothelium dysfunction which gives a clue in identificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
163
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(173 citation statements)
references
References 160 publications
(155 reference statements)
0
163
0
10
Order By: Relevance
“…A possible mechanism for this relationship is that coffee has been found to be inversely associated with endothelia dysfunction, which is a major cause of the development of cerebral SV disease. 29 Coffee contains many antioxidant and anti-inflammatory components such as caffeine, chlorogenic acid, and diterpenes. 30 In addition, chlorogenic acid protects neurons from glutamate neurotoxicity by regulating Ca 2+ entry into neurons.…”
Section: Discussionmentioning
confidence: 99%
“…A possible mechanism for this relationship is that coffee has been found to be inversely associated with endothelia dysfunction, which is a major cause of the development of cerebral SV disease. 29 Coffee contains many antioxidant and anti-inflammatory components such as caffeine, chlorogenic acid, and diterpenes. 30 In addition, chlorogenic acid protects neurons from glutamate neurotoxicity by regulating Ca 2+ entry into neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing data have implicated endothelial damage as a key process in the pathogenesis of small vessel disease . Experimental studies have shown that elevated tHcy levels can lead to alterations within the blood vessel wall .…”
Section: Discussionmentioning
confidence: 99%
“…1 The disease has multifarious etiology and pathogenesis, the most common form being arteriolosclerotic CSVD (A-CSVD), which is also known as age-and vascular risk-factor-related CSVD. 2 Recurrent minor strokes, blood-brain barrier (BBB) impairment, inflammatory responses and leukocyte infiltration are classical pathological features of CSVD. 3 The inflammatory reaction is triggered both at the onset of ischemic and hemorrhagic stroke (attack phase) 4 and chronic stages (remitting phase) of "silent CSVD".…”
Section: Introductionmentioning
confidence: 99%